Synthesis of flavonoid derivatives as anti-rheumatoid arthritis agent: A systematic literature review and meta-analyses - Andy Eko Wibowo, Ratna Asmah Susidarti, Ika Puspitasari, Sabtanti Harimurti (Journal of Applied Pharmaceutical Science, 2025)
Flavonoids are plant-derived compounds with anti-inflammatory, antioxidant, and immunomodulatory properties, offering potential as adjunct therapies for rheumatoid arthritis (RA). This review explores their synthesis and therapeutic potential in RA. Following preferred reporting items for systematic reviews and meta-analyses guidelines, 324 articles were screened; 33 studies met the inclusion criteria, encompassing in silico, in vitro, and in vivo evaluations, along with diverse synthesis approaches. A meta-analysis was conducted on selected studies with comparable quantitative data to evaluate the overall effect size of flavonoid derivatives on key inflammatory markers. Structural modifications (particularly hydroxyl and methoxy groups) enhanced anti-inflammatory effects. Flavonoids inhibited TNF-α, IL-1, IL-6, modulated immune pathways, and reduced oxidative stress. The meta-analysis supported the significant inhibitory effects of flavonoid derivatives on pro-inflammatory cytokines, reinforcing their therapeutic potential. Flavonoids demonstrate promising multi-target activity and safety profiles for RA management. However, meta-analytic findings highlight variability in study quality and outcomes. Further research is needed to optimize synthesis, improve bioavailability, and validate efficacy through clinical trials.
Keywords: Anti-inflammatory, pharmacological evaluation, flavonoids, rheumatoid arthritis, flavonoid synthesis